(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2025)
Develop sustainability in organic chemistry represented to the students by include the green chemistry principal in organic synthesis learning. This study showed the synthesis organic laboratory project by using retrosynthesis analysis to increase students understanding about the green chemistry. The participants were 28 students in in the third year of one state university in Indonesia. The findings of this study show there is a connection between conceptual knowledge in laboratoy project using the retrosynthetic analysis that will lead to Green chemistry concept about sustainability developing. It is known that the biggest stage of the retrosynthetic approach of students is in identify characteritics of Benzoin by using literature in media online and software offline. Even students between groups had no significant differences in skill outcomes at the 5% confidence level. It is suggests to carried out learning using project-based learning in organic synthesis and so that they will develop all the student abilities in synthetic organic compounds.